The effect of graphic organizer strategy on students’ reading comprehension of grade eleventh of SMA YP HKBP 1 Pematangsiantar - Silalahi, Brooklyn Fransius Bonatua; Napitupulu, Selviana; Hutauruk, Bertaria Sohnata (Lembaga Riset Mutiara Akbar, 2026)
This research investigates the effect of the Graphic Organizer strategy on students’ reading comprehension of narrative texts, focusing specifically on literal and inferential understanding. The study employed a quasi-experimental design involving two eleventh-grade classes of SMA YP HKBP 1 Pematangsiantar. An experimental class was taught using story-map graphic organizers, and a control class was taught using conventional reading instruction. Both groups were given a pre-test and post-test to measure their comprehension before and after the treatment. The results of the descriptive analysis showed that both classes improved after instruction; the experimental class increased from a mean score of 63.81 to 85.71, while the control class improved from 75.00 to 89.52. Paired sample t-test results indicated significant improvement within each group. However, the independent sample t-test showed no statistically significant difference between the post-test scores of the two groups (Sig. = .228 more than 0.05). This finding indicates that although the Graphic Organizer strategy helped students improve their comprehension and organize narrative information more effectively, it was not significantly more effective than the conventional method within the duration and conditions of this study.